Validity and Effectiveness of Argument-Driven Inquiry Model With Contextual Approaches to Improve Critical Thinking Skills in Science Learning - Siti Fadilah. MS; Budi Jatmiko; Tjipto Prastowo (Studies in Learning and Teaching, 2020)
This study aimed to determine the effectiveness and validity of a teaching document using Argument-Driven Inquiry (ADI) model with a Contextual Approach to improve students' critical thinking skills in science learning. This type of research was research and development (R&D) that refers to the 4D model. Data collected by the validation sheets, student response sheet, and critical thinking skills test. They were analyzed by using t-test and N-gain. The present research was applied in lower secondary at SMP Negeri 1 Bluto with trial design of One-Group Pretest-Posttest Design. The results of the data analysis show that (1) the learning materials was valid in terms of the results of the validity of the materials with the score of 3.57; (2) learning materials was effective in terms of: (a) the students' responses were categorized as very good with results of 83.2%, (b) students' critical thinking skill increased with an average value of N-gain in grade eight A of 0.74 and 0.75 for grade eight B with a high category. Based on the results of statistical analysis using the t test, the probability value (sig) was 0,000 in the two classes. This means that the significance value was less than 0.05 which means there was a significant difference between the pre-test and post-test results. In conclusion, Argument-Driven Inquiry (ADI) model with a Contextual Approach is proven to be feasible and effective for improving critical thinking skills.